The fate of O(N) multi-critical universal behaviour - Defenu, Nicolò; Codello, Alessandro (Arxiv, 2020)
The multi-critical fixed points of $O(N)$ symmetric models cease to exist in the $N→∞$ limit, but the mechanism regulating their annihilation still presents several enigmatic aspects. Here, we explore the evolution of high-order multi-critical points in the $(d,N)$ plane and uncover a complex mosaics for their asymptotic behaviour at large $N$. This picture is confirmed by various RG approaches and constitutes a fundamental step towards the full comprehension of critical behaviour in $O(N)$ field theories.
Gesehen am 14.09.2022